Silencing tumor necrosis factor-alpha in vitro from small interfering RNA-decorated titanium nanotube array can facilitate osteogenic differentiation of mesenchymal stem cells - Wang Z (Dove Medical Press, 2016)
Zhenlin Wang,1,* Zhiqiang Hu,2,* Dawei Zhang,3 Mengchuan Zhuo,1 Jiwei Cheng,1 Xingping Xu,1 Yongming Xing,1 Jie Fan2 1Department of Orthopaedics, 2Department of Otorhinolaryngology, No 113 Hospital of PLA, Ningbo, 3Department of Orthopaedics, Xijing Hospital of PLA, Xi’an, People’s Republic of China *These authors contributed equally to this work Abstract: Titanium implants are known for their bone bonding ability. However, the osseointegration may be severely disturbed in the inflammation environment. In order to enhance osseointegration of the implant in an inflamed environment, the small interfering RNA (siRNA) targeting tumor necrosis factor alpha (TNF-α) was used to functionalize titanium surface for gene silencing. The chitosan–tripolyphosphate–hyaluronate complexes were used to formulate nanoparticles (NPs) with siRNA, which were adsorbed directly by the anodized titanium surface. The surface characterization was analyzed by scanning electron microscope, atomic force microscopy, as well as contact angle measurement. The fluorescence microscope was used to monitor the degradation of the layer. The coculture system was established with mesenchymal stem cells (MSCs) grown directly on functionalized titanium surface and RAW264.7 cells (preactivated by lipopolysaccharide) grown upside in a transwell chamber. The transfection and knockdown efficiency of TNF-α in RAW264.7 cells were determined by fluorescence microscope, quantitative polymerase chain reaction, and enzyme-linked immunosorbent assay. The cytoskeleton and osteogenic differentiation of MSCs were also analyzed. Regular vertical aligned nanotubes (~100 nm diameter and ~300 nm length) were generated after anodization of polished titanium. After loading with NPs, the nanotubes were filled and covered by a layer of amorphous particles. The surface topography changed and wettability decreased after covering with NPs. As expected, a burst degradation of the film was observed, which could provide sufficient NPs in the released supernatant and result in transfection and knockdown effects in RAW264.7 cells. The cytoskeleton arrangement of MSCs was elongated and the osteogenic differentiation was also significantly improved on NPs loading surface. In conclusion, the siRNA decorated titanium implant could simultaneously suppress inflammation and improve osteogenesis, which may be suitable for peri-implant bone formation under inflammatory conditions. Keywords: titanium, siRNA, TNF-alpha, nanoparticles, osteogenic differentiation